Characterization Of Coal Mine Panels In Bord And Pillar Workings In Respect Of Their Proneness To Spontaneous Heating - A Prediction Model - T. R. Roy (The Southern African Institute of Mining and Metallurgy, 2003)
A prediction model, developed by Central Mining Research Institute (India) for evaluation of fire risk rating of underground coal mine panels in bord and pillar working in respect of their proneness to spontaneous heating, is presented in this paper. The concept used in this model is innovative and user friendly. This model may be applied to a panel where extraction is carried out using any of the techniques: i) depillaring with formation of small pillars as final operation, ii) extraction by broadening of galleries, iii) depillaring with hydraulic sand stowing, and iv) depillaring with caving. Here, major fire risk parameters are short-listed and divided into three broad groups in accordance with the nature of their contribution to the spontaneous heating of a mine panel. The paper describes the procedure for estimating the fire risk rating of individual groups using separate objective type models developed for this purpose. Then it evaluates the overall fire risk rating of the panel by combining the fire risk ratings of all the three broad groups. The model is tested with the field data collected from different collieries spreading across the country and with the laboratory data for critical assessment of fitness. Keywords : prediction model, fire risk rating of panel, spontaneous heating of coal, underground panel, bord and pillar working.